Pengembangan Media (TPQ) Tangga Pintar QR Code dengan Nilai Keislaman Materi Jaringan Tumbuhan di Tingkat SMA/MA - Venty Zuslia Rinduwan; Achmad Ali Fikri (Institut Agama Islam Negeri Kerinci, 2023)
The purpose of this study was to develop smart ladder QR code media (TPQ) with Islamic values ​​and determine the feasibility of developing TPQ media with Islamic values ​​of plant tissue material at the SMA/MA level. This type of research used R&D with a 4D development model, was tested at MA NU Hasyim Asy'ari 2 Kudus with research subjects as many as 29 students from class XI MIPA and XI MIPA Tahfidz MA NU Hasyim Asy'ari 2 Kudus who had received plant tissue material. Data collection using expert validation questionnaires and the results of development media trials. The sampling technique used probability sampling technique with random clusters, analyzed using percentage formula analysis from Nawal Sartika Sari and rasch model analysis. The results of this development research are media expert validation assessments getting a score of 88.64% in the